NUMERICAL ANALYSIS ON THE EFFECT OF DILUTED HYDROGEN FUEL BY A FIXED AMOUNT OF SUPPLIED HYDROGEN USING A QUASI-THREE-DIMENSIONAL SOLID OXIDE FUEL CELL MODEL - W. C. Tan, W. C. Tan; E. A. Lim, E. A. Lim; E. M. Cheng, E. M. Cheng; W. H. Tan, W. H. Tan; H. A. Rahman, H. A. Rahman (2023)
Solid oxide fuel cell (SOFC) has excellent fuel flexibility for various fuels. Despite some drawbacks like storage and transportation, hydrogen stands up as the best fuel for SOFC. Hydrogen fuel is diluted non-reactive gas species before it is supplied to the SOFC. In this study, a quasi-three-dimensional SOFC model with real microstructure is used to analyse the effect of the diluted fuel mixture. The hydrogen fuel is diluted with nitrogen and a small amount of steam. The mole amount of hydrogen within fuel mixtures is kept constant. On the other hand, the air that is supplied to the air channel of the SOFC remains unchanged. It is found that the cell that is supplied with the highest concentration of hydrogen has the highest performance due to its high partial pressure of hydrogen within the fuel mixture. Such a high partial pressure promotes a low anode concentration loss. Also, the cell that is supplied with a low hydrogen concentration is unable to benefit from its high average cell temperature as its performance is drained by the low partial pressure of hydrogen within the fuel mixture.